Readings. The Emergence of Complex Societies. Patterns in Human History - Anonymus, A. (1971)
A course of study prepared by the Anthropology Curriculum Study Project of the American Anthropological Association Supported by the National Science Foundation; Jarmo; Deciphering Cuneiform Writing; Cuneiform Text Translation; Diane E. Taylor, Two Sumerian Statues; Jarmo to Sumer to Babylon; Cities, Kings, and Gods; An Anthropological View of Sumerian Religion; Diane E. Taylor, Mesopotamian Archaeology: Seizure and Search); Teaching Plan v-63 p.